Autograft versus sterilized allograft for lateral calcaneal lengthening osteotomies: Comparison of 50 patients. Issue 30 (July 2016) - Müller, Sebastian A.; Barg, Alexej; Vavken, Patrick; Valderrabano, Victor; Müller, Andreas M.
Abstract : Abstract: Sterilized allografts may be less resistant to collapse and prone to nonunion leading to loss of correction in open wedge osteotomies. These adverse events usually occur at early time points (i.e., < 9 months postoperatively). The goal of this study was to compare sterilized allografts to autologous grafts in respect to secondary loss of hindfoot alignment and graft incorporation after lateral calcaneal lengthening osteotomies. Fifty patients (22 F/ 28 M, age: 16–69 years) who had undergone 50 lateral calcaneal lengthening osteotomies for adult flatfoot deformity were included in this retrospective study. Cortical sterilized allografts were used in 25 patients, autologous grafts in the remaining 25. Patients' preoperative, 6 and 12 weeks, and 6 to 9 months follow-up weight-bearing radiographs of the affected foot were analyzed by 2 blinded radiologists: on each radiograph, graft incorporation, the talo-first metatarsal angle (TFMA), the talo-navicular coverage angle (TNCA), and the calcaneal pitch angle (CPA) were assessed. Loss of hindfoot alignment was defined as an increase of the TFMA or the TNCA or a decrease of the CPA, each by 5°. Inter- and intraclass correlation coefficients for TFMA, TNCA, and CPA measurements ranged from 0.93 to 0.99. At all follow-up visits, the ratio of patients with loss of hindfoot alignment and graft incorporation was not significantly different between the allograft and autograft group. However, loss of correction was associated with failure of graft incorporation. Compared with autografts, sterilized allografts do not increase the risk for loss of hindfoot alignment in lateral column lengthening of the calcaneus. With respect to mechanical resistance, allografts thus mean an equal and valid alternative without risk of donor site morbidities.